Study on the mechanical properties of bottom ash as a partial sand replacement in a non-load bearing fly ash bricks - Doh, Shu Ing; Alhokabi, Abdulmajeed Ali (Saudi Journal of Civil Engineering, 2019)
The worldwide production of coal ashes is estimated to more than 800 million tonnes in 2012. Coal use is forecast to rise over 50% to 2030, with developing countries responsible for 97% of this increase worldwide. The estimated worldwide production of coal ashes is around 13.33 billion tonnes in 2030. The reuse rate for fly ash is around 47% whereas the reuse of bottom ash is only around 5.28%. It has contributed to environmental problems such as contaminating ground and surface water due to the limitation of dumping space, where it is still treated as waste and put in impoundment ponds, silos or landfills. By using Coal waste to replace cement production, the environmental benefits will occur and lead to a decrease in CO2 emissions by 0.9 tonnes for each ton of fly Ash used. According to the Environmental Protection Agency (EPA), living next to a coal ash disposal site can increase the human health risk of cancer or other diseases. It can also affect drinking water from a well where humans may get cancer from drinking water contaminated with arsenic. In Malaysia, there is seven coal-fired electric power station for the time being. In Peninsular Malaysia, there is four coalfired electric power station that produced at least 1400 MW of electric power. Coal waste is produced which includes coal ash in the fraction of about 75-85 % Fly Ash (FA) and 15-25 % Bottom Ash (BA). The study was conducted using the waste products from Tanjung Bin power plant which located in Mukim Serkat, Daerah Pontian, Johor, Malaysia that started operation in September 2006 with a capacity of (2100MW) electricity generating capacity. It is one of the four thermal power plants that utilize pulverized coal in the generation of electricity. Tanjung Bin power station produces 180 tonnes per day of bottom ash and 1,620 tonnes per day of fly ash from 18,000 tonnes per day of coal. This study presents the results of an experimental investigation on the probability of using Bottom-ash products in producing Fly-Ash bricks. By substituting 20% of cement with FA and fine aggregate (river sand) with partial replacement of 5%,10%,15% and 20% of BA where sand replacement can save the natural sand resources from depletion and also reduce the coal ash (CA) in Malaysia which classified under the Scheduled Waste (SW 104) Environmental Quality Act. The results of compressive strength at 7,14 & 28 days of air curing showed that the compressive strength and flexural strength decrease with the increasing of sand replacement of the bottom ash while noticed a visible increment of the water absorption ratio with increasing BA percentage wheras density shows the opposite of that.